What is -2(x-3) how do i answer this question?

Answers

Answer 1
Answer:


-2(x-3)

= -2x+6

-2*x=-2x and -2*-3=6

Answer 2
Answer: -2(x-3)=
= -2 * x+2*3=
=-2x+6

Related Questions

Match the term with the definition. Match Term Definition corresponding angles A) the constant by which a figure (or the dimensions of a figure) increases or decreases scale factor B) corresponding sides of two similar triangles proportional C) figures that have congruent angles and corresponding sides that are proportional to one another similar polygons D) these corresponding parts are congruent, given two similar triangles scale drawing E) a depiction of a real object with accurate sizes except they have all been reduced or enlarged
Triangle ABC underwent a sequence of transformations to give triangle A′B′C′. Which transformations could not have taken place? A. a reflection across the line y = x followed by a reflection across the line y = -x B. a reflection across the x-axis followed by a reflection across the y-axis C. a rotation 180° clockwise about the origin followed by a reflection across the line y = x D. a reflection across the y-axis followed by a reflection across the x-axis
Cual es la mitad de 1.5
Prime factorization of 147
Find the area of triangle of 7m 9m

Please help and thank you! (x4)

Answers

in rectangular form the equation is

Check all that apply. The center of gravity of a triangular solid with uniform thickness and density is... A. The point at which one can balance the triangle.
B. The point shared by a triangle's altitudes.
C. The centroid.
D. The orthocenter.

Answers

The answers are options A and C. The center of gravity of a triangular solid with uniform thickness and density is the centroid which is the point at which one can balance the triangle. It is the center of mass of an object with uniform density.

GIVING BRAINIEST
Explain how u got your answer
Pick from 1. 2. And 3.

Answers

Answer:

#2 is not a function

Step-by-step explanation:

Although there can be multiple y-values attributed to a single x-value, there can only be ONE x-value(of a number) in a function, so #2 would be incorrect seeing as it uses the x-value, 2, two times.

What is the seventh term of the sequence whose nth term is (n + 1)(n − 2)?A.) 28

B.)35

C.) 36

D.) 40

Answers

To do this, you simply substitute 7 into the equation. 

[(7) + 1][(7) − 2]
BODMAS tell us that we should do the sum in the brackets before anything else. 
(8)(5)
8 X 5 = 40

The seventh term is 40. The answer is D)

If f(x)=64-x2 and g(x)=8-x which is the rule of the function (f + g)(x)?

Answers

(f+g)(x)=f(x)+g(x)\n\n(f+g)(x)=64-x^2+8-x\n(f+g)(x)=-x^2-x+72

Find the distance between (–3, –3) and (6, 12). Round the answer to the nearest hundredth, if necessary.

Answers

A=(x_A;y_A)\ \ \ and\ \ \ B=(x_B;y_B)\n\n \Rightarrow\ \ \ |AB|= √((x_A-x_B)^2+(y_A-y_B)^2) \n----------------------\n\nA=(-3;-3);\ \ \ B=(6;12)\n\n|AB|= √((-3-6)^2+(-3-12)^2) =\n\n.\ \ \ \ \ \ = √(81+225) = √(306) =3 √(34) \approx17.49
(-3, -3), \ \ (6, 12)\n \ndistance \ formula : \n \nd =\sqrt{(x_(2)-x_(1))^2 +(y_(2)-y_(1))^2} \n \nd =√((6-(-3))^2 +(12-(-3) )^2) =√((6+3)^2 +(12+3 )^2) =√(9^2+15^2)=\n \n=√(81+225)=√(306)=√(9\cdot 34)=3√(34)=3\cdot 5.83= 17.49